CORRELATION BETWEEN SHUTTLE RUN TEST AND 200 METERS RUN TEST IN MILITARY POLICE OF THE PUBLIC SECURITY TECHNICAL COURSE (Fiep Bulletin - online, 2011)
INTRODUCTION: In the Military Police of Minas Gerais (PMMG), the practice of physical activities receives a greater importance due to the peculiarities of the function of the military police. In his job, the military police needs a good physical condition to, beyond maintaining mental and physical healthiness; execute in the best way his obligations. The students of the formation courses of PMMG are evaluated in 200 meters run (velocity) and shuttle run (agility). OBJECTIVE: The purpose of this study is establishing the relationship level between the 200 meter and Shuttle Run test which the Military Police of the Public Security Technical Course is submitted. METHODOLOGY: 89 male military police of the PMMG´s Technical Education Center, with age between 19 to 30 were selected. The 200 meters run were applied in a track and field track and the shuttle run test were applied in a specific place, and both places are part of the PMMG´s sport complex. STATISTICAL ANALYSIS: To analyze the correlation and association level between the 200 meters and Shuttle Run test Pearson correlation was applied (p
Keywords: shuttle run; 200 meter run; military police